2022
DOI: 10.1007/s11696-022-02242-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vitro cytotoxicity assessment of nanoemulsified lawsone

Abstract: Lawsone is a biomolecule that belongs to the naphthoquinone class found in henna leaves. This quinone is widely used in cosmetic products being considered the oldest coloring agent applied for dyeing hair. Moreover, biological activities have been attributed to lawsone such as antibacterial, antifungal, and anticancer. However, these activities are mostly limited due to its low aqueous solubility and chemical instability. In this context, this study aimed to develop nanoemulsion containing lawsone (NE-law) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Performing free radical scavenging assay, we also showed that LWS-PLGA-FA-CS nanoparticle efficiently inhibited the ABTS and DPPH radicals, which is in agreement with previous reports regarding the antioxidant properties of different derivatives of Henna [51,52]. We found out that LWS-PLGA-FA-CS nanoparticles possessed both bactericidal and bacteriostatic activites against E.Coli and P. aeruginosa as well, which is in agreement with previous reports [8,15,17]. Abadehie et al also introduced Lawsone encapsulated chitosan mat as a potent antibacterial wound dressing [14].…”
Section: Effect Of Lws-plga-fa-cs On Target Genes Expressionsupporting
confidence: 92%
See 3 more Smart Citations
“…Performing free radical scavenging assay, we also showed that LWS-PLGA-FA-CS nanoparticle efficiently inhibited the ABTS and DPPH radicals, which is in agreement with previous reports regarding the antioxidant properties of different derivatives of Henna [51,52]. We found out that LWS-PLGA-FA-CS nanoparticles possessed both bactericidal and bacteriostatic activites against E.Coli and P. aeruginosa as well, which is in agreement with previous reports [8,15,17]. Abadehie et al also introduced Lawsone encapsulated chitosan mat as a potent antibacterial wound dressing [14].…”
Section: Effect Of Lws-plga-fa-cs On Target Genes Expressionsupporting
confidence: 92%
“…In this line, Barani et al used lawsoneencapsulated niosome against MCF-7 breast cancer cell line and reported an enhanced antitumour activity [15]. Another study applied nanoemulsifed lawsone and reported an improved in vitro cytotoxicity against cervical carcinoma cells [17]. Rasouliyan et al study on a lung cancer cell line indicated that lawsone-loaded solid lipid nanoparticles induced apoptosis and necrosis, and downregulated BCL-2 expression, which is in agreement with the present findings [16].…”
Section: Effect Of Lws-plga-fa-cs On Target Genes Expressionsupporting
confidence: 87%
See 2 more Smart Citations
“…[61] Nanoemulsified lawsone (NE-law) showed improved in vitro cytotoxicity against cervical carcinoma cells compared to free lawsone, making it a stable and promising formulation for further development. [62] Bacterial cellulose incorporating dendrimer, chitosan, Henna, Green tea, and Malva sylvestris exhibited antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa. The samples showed good biocompatibility and controlled drug release, with Green tea demonstrating the most potent antimicrobial effect.…”
Section: Excellent Bioavailability and Sustained Release Of Gemcitabi...mentioning
confidence: 99%